Positive rate and risk factors of latent tuberculosis infection among persons living with HIV in Jiangsu Province, China - Zhang, Yu; Lu, Peng; Wu, Kai; Zhou, Hongxi; Yu, Haibing; Yuan, Ju; Dong, Lang; Liu, Qiao; Lu, Wei; Yang, Haitao; Cao, Dianyi; Zhu, Limei (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To analyze the latent tuberculosis infection (LTBI) among persons living with HIV(PLWH) in Jiangsu Province, to explore the factors affecting the positive rate of LTBI, and to take appropriate measures to control tuberculosis (TB) infection. Methods: A cross-sectional study was conducted among PLWH in Jiangsu Province from June to July 2021. All PLWH in Jiangsu Province were used as the study population. Currently, the diagnosis of LTBI lacks a "gold standard" and can only be assisted by the immunological method. In this study, Tuberculin skin test (TST), ESAT6-CFP10 test (EC), and QuantiFERON-TB gold in-tube (QFT) were used to detect the positive rate of LTBI among PLWH and to analyze their risk factors. Results: A total of 340 prisoners were included, 89.7% were male, the median age was 38 years [Interquartile Range (IQR):32-46 years], these patients were on Antiviral Therapy (ART), and median CD4 counts was 376 (IQR: 261-496), 103 (30.3%) were positive in at least one test, LTBI by TST was 16.5%, LTBI by EC was 15.9%, LTBI by QFT was 26.2%. Univariate analysis showed the results for TST, EC, and QFT were not affected by CD4 counts (p>0.05), and multivariate analysis showed that a history of incarceration was associated with an increased risk of positive TST (adjusted odds ratio [aOR]=1.98;95% CI,1.03-3.82), EC (aOR=2.65;95% CI,1.37-5.12) and QFT (aOR=2.01;95%CI,1.12-3.57), in addition, female gender was associated with increased risk of positive TST (aOR=3.66;95%CI,1.60-8.37) and EC (aOR=3.43;95%CI,1.46-8.07), and contact history of TB patients was associated with increased risk of TST (aOR= 2.54;95%CI,1.23-5.22) and QFT (aOR=2.03;95%CI,1.03-3.99), and ethnic minorities (aOR=0.26;95%CI,0.12-0.57), longer duration of incarceration was associated with an increased risk of positive QFT (aOR=1.12;95%CI,1.02-1.24). Conclusions Female gender, and ethnic minorities, history of incarceration, longer duration of incarceration, and contact history of TB patients are risk factors for LTBI among PLWH in Jiangsu Province, and attention should be paid to TB control in this population.